Low-grade Fibromyxoid Sarcoma: Treatment Outcomes and Efficacy of Chemotherapy - CHAMBERLAIN, FLORENCE (In Vivo, 2020)
Background: Low-grade fibromyxoid sarcoma (LGFMS) is a rare sarcoma subtype with a generally indolent pattern of clinical behaviour, but treatments for advanced disease are limited. Patients and Methods: A retrospective search of a prospectively maintained institutional database identified 102 patients treated from December 1994 to August 2018. We evaluated the outcome of patients and the efficacy and safety of non-surgical therapies in LGFMS. Results: Ninety-four out of 102 (92.2%) underwent primary resection, seven (6.9%) were treated with systemic therapy and one (1.0%) is currently being treated with pre-operative radiotherapy. The RECIST 1.1 response rate to first-line chemotherapy was 0%, and median progression-free survival was 1.84 months (95% confidence intervaI=0.10-3.6 months). Conclusion: Conventional systemic therapy has limited efficacy in advanced LGFMS.